Pi of the sky telescopes in Spain and Chile - Siudek, M.; Batsch, T.; Castro-Tirado, A.; Czyrkowski, H.; Cwiok, M.; Dabrowski, R.; Jelínek, M.; Kasprowicz, G.; Majcher, A.; Majczyna, A.; Malek, K.; Mankiewicz, L.; et al. (Ceske Vysoke Uceni Technicke, 2011)
Pi of the Sky is a system of robotic telescopes designed for observations of short timescale astrophysical phenomena, e.g. prompt optical GRB emissions. The apparatus is designed to monitor a large fraction of the sky with 12-13 m range and time resolution of the order of 1-10 seconds. In October 2010 the first unit of the new Pi of the Sky detector system was successfully installed in the INTA El Arenosillo Test Centre in Spain. We also moved our prototype detector from Las Campanas Observatory to San Pedro de Atacama Observatory in March 2011. The status and performance of both detectors is presented.